GANGRENOUS MASTITIS IN A FEMALE BEAGLE DOG - MURALI, REVATHY M; R S, ABHILASH; V K, VIDYA; PRATHAP, GAYATHRI; BABU, ANILA (The Indian Journal of Animal Reproduction, 2021)
A three year old female beagle dog, whelped 7 days back, was presented to the University Veterinary Hospital,Kokkalai with a complaint of reduced food intake and death of puppies. An oedematous right caudal mammary glandwhich was hot to touch and have sticky milk secretions. Milk sample was collected and examined for culture andsensitivity examination. The mammary gland underwent gangrenous changes and sloughing off happened for thetissue. The animal was treated with antibiotics and fluid therapy. The wound was managed with local applications andwet to dry dressing. After three week of post therapy a scar formed on recovered area and animal showed anuneventful recovery.
Keywords: Gangrene; Mastitis; Antibiogram; sloughing off; scar